Risk factors associated with mortality in neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) and clinical implications - Kuerbanjiang Abuduxikuer; Rui Chen; Zhong-Lin Wang; Jian-She Wang (BMC, 2019)
Abstract Background Neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) has high prevalence in East Asia, and has been reported in other parts of the world. NICCD is also the most common form of genetic cholestasis among East Asians. There has been reports of mortalities or liver transplants associated with NICCD, but risk factors associated with poor outcome were unknown. Our objective is to report NICCD mortalities in a tertiary pediatric hepatology center, and to explore associated risk factors along with implications to clinical practice. Method This is a retrospective analysis of NICCD cases collected from June 2003 until January 2017 in the Children's Hospital of Fudan University. Clinical, biochemical, and genetic data were compared between deceased cases and survivors without liver transplant. Results Sixty-one confirmed NICCD cases, including 52 cases in the survival group, and 9 cases in the mortality group, were included in the analysis. Mean age at referral in the mortality group was significantly higher when compared to the survival group (9.58 ± 5.03 VS 3.96 ± 3.13 months, p < 0.000). The proportion with infection in the mortality group was significantly higher than the survival group (p = 0.023). 44.4% of patients in the mortality group did not receive lactose-free and/or medium chain triglycerides enriched (LF/MCT) formula, and this percentage was significantly higher than the survival group (9.6%, p = 0.021). Mean platelet (PLT) count in the mortality group was significantly lower than the survival group (p = 0.010). Mean serum gamma-glutamyl transpeptidase (GGT), and total cholesterol (TCH) levels were significantly lower in the mortality group when compared to the survival group with p values of 0.001, and 0.019, respectively. Those who died had higher serum ammonium levels than survivors (p = 0.016). Mean level of citrulline was significantly lower in the mortality group compared to the survival group (p = 0.010). On the other hand, mean level of tyrosine was significantly higher in the mortality group than that of the survival group (p = 0.015). Conclusion Late referral, presence of infection, delayed treatment with LF/MCT formula, lower platelet count, lower levels of GGT, total cholesterol, blood citrulline, and higher level of blood ammonia and tyrosine, were associated with poor prognosis in NICCD.